Critically Important: The Heterogeneous Effect of Diplomatic Tensions on Trade - Julian Hinz; Elsa Leromain (Review of Industrial Organization, 2020)
With global value chains interlocking today's economies, what is the impact of diplomatic tensions on international trade? We exploit variation in monthly data on imports, a measure of imported input use in the domestic economy, and the incidence of bilateral diplomatic tensions to show that their impact on trade is heterogeneous across countries and industries. Trade in industries that are crucial for domestic production is more sensitive to political tensions. We expose the underlying mechanism in a simple framework before testing it in reduced form.
Keywords: 330; Diplomatic tensions; Political relations; Trade